Identification of oleoylethanolamide as an endogenous ligand for HIF-3α - Xiaotong Diao; Fei Ye; Meina Zhang; Xintong Ren; Xiaoxu Tian; Jingping Lu; Xiangnan Sun; Zeng Hou; Xiaoyu Chen; Fengwei Li; Jingjing Zhuang; Hong Ding; et al. (Nature Communications, 2022)
Whether hypoxia-inducible factors (HIFs) can be directly regulated by endogenous small molecules is a long-standing question. Here authors identified the metabolite oleoylethanolamide as a HIF-3α ligand and further revealed its mechanism of action.